Human RTEL1 stabilizes long G-overhangs allowing telomerase-dependent over-extension. Issue 9 (7th March 2018) - Porreca, Rosa M; Glousker, Galina; Awad, Aya; Matilla Fernandez, Maria I; Gibaud, Anne; Naucke, Christian; Cohen, Scott B; Bryan, Tracy M; Tzfati, Yehuda; Draskovic, Irena; Londoño-Vallejo, Arturo
Abstract: Telomere maintenance protects the cell against genome instability and senescence. Accelerated telomere attrition is a characteristic of premature aging syndromes including Dyskeratosis congenita (DC). Mutations in hRTEL1 are associated with a severe form of DC called Hoyeraal-Hreidarsson syndrome (HHS). HHS patients carry short telomeres and HHS cells display telomere damage. Here we investigated how hRTEL1 contributes to telomere maintenance in human primary as well as tumor cells. Transient depletion of hRTEL1 resulted in rapid telomere shortening only in the context of telomerase-positive cells with very long telomeres and high levels of telomerase. The effect of hRTEL1 on telomere length is telomerase dependent without impacting telomerase biogenesis or targeting of the enzyme to telomeres. Instead, RTEL1 depletion led to a decrease in both G-overhang content and POT1 association with telomeres with limited telomere uncapping. Strikingly, overexpression of POT1 restored telomere length but not the overhang, demonstrating that G-overhang loss is the primary defect caused by RTEL1 depletion. We propose that hRTEL1 contributes to the maintenance of long telomeres by preserving long G-overhangs, thereby facilitating POT1 binding and elongation by telomerase.